2014
DOI: 10.1007/s10067-014-2753-5
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound assessment of enthesis thickening in psoriatic arthritis patients treated with adalimumab compared to methotrexate

Abstract: The objective of the study was to combine ultrasonographic (US) with clinical findings for comparing the effect of adalimumab (ADA) to methotrexate (MTX) on the thickness of tendons and enthesis in psoriatic arthritis (PsA) patients. Forty-three consecutive PsA patients were examined at baseline and after 6 and 12 weeks of treatment with ADA or MTX. The US assessment included thickness measurement of the extensor (ET) and flexor tendons (FT) of the second and third finger of both hands, plantar aponeurosis (PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
7
1
Order By: Relevance
“…There is no data available on the effectiveness of methotrexate in the treatment of distal interphalangeal joint extensor tendon enthesopathy in patients with nail psoriasis. In a study by Litinsky et al, no change on US was observed in the thickness of the extensor and flexor tendons of the second and third fingers of both hands measured above the MCP joint line before and after 3 months of therapy with methotrexate in PsA patients [33]. In our study, methotrexate treatment resulted in a decrease of the extensor tendon thickness only in patients with Ps but not in PsA.…”
Section: Discussioncontrasting
confidence: 65%
“…There is no data available on the effectiveness of methotrexate in the treatment of distal interphalangeal joint extensor tendon enthesopathy in patients with nail psoriasis. In a study by Litinsky et al, no change on US was observed in the thickness of the extensor and flexor tendons of the second and third fingers of both hands measured above the MCP joint line before and after 3 months of therapy with methotrexate in PsA patients [33]. In our study, methotrexate treatment resulted in a decrease of the extensor tendon thickness only in patients with Ps but not in PsA.…”
Section: Discussioncontrasting
confidence: 65%
“…Five papers did not meet the eligibility criteria and were removed, thus 15 papers were included ( Table 3 ) [ 3 , 10 , 30–42 ]. The date of publication ranged from 2000 [ 36 ] to 2020 [ 31 , 34 ], with studies from Italy [ 30 , 32 , 34 , 36–38 ], Egypt [ 31 , 33 ], the UK [ 35 , 40 ], Kuwait [ 3 ], Israel [ 42 ], Norway [ 10 ], China [ 41 ] and The Netherlands [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies identified PsA patients as a ‘control’ group (one as ‘inactive’ PsA and one comparing psoriasis to PsA) [ 3 , 33 ]. The majority of studies focussed exclusively on PsA [ 3 , 10 , 30 , 35 , 36 , 38–40 , 42 ]; however, other comparator groups included patients with psoriasis [ 33 , 41 ], FM [ 34 , 37 ], SpA [ 31 ] and other types of arthritis [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, only few pilot studies have assessed the US ability to detect treatment induced changes at entheseal level in a limited number of PsA patients [ 63 , 64 ].…”
Section: Monitoring Response To Treatmentmentioning
confidence: 99%
“…The scanning protocol was quite unusual, assessing only tendon thickness and including entheses (Achilles tendon and plantar fascia calcaneal insertions), tendons without synovial sheath (extensor digitorum tendons at the level of 2nd and 3rd metacarpophalangeal joints) and tendons with synovial sheath (flexor digitorum tendons at the level of 2nd and 3rd metacarpophalangeal joints). They found a trend towards a higher reduction in thickness of Achilles tendon and plantar fascia in the adalimumab group, even if the lack of PD examination represents a relevant limitation of this study [ 64 ].…”
Section: Monitoring Response To Treatmentmentioning
confidence: 99%